Psychological burden and psychohygiene among social workers in palliative care: Psychological burden and psychohygiene among social workers in palliative care (Paliativní medicína, 2025)
The aim of this article is to analyse the psychological burden of social workers in palliative care and identify sources of support that contribute to maintaining their mentalhealth. Theoretical part of the article deals with the specifics of social work in the context of palliative care, particularly in the hospital setting. For the research part, the following method was chosen qualitative research strategy using semi-structured interviews. Researchfocused on health and social workers in hospital palliative care.